Methods of Multivariate Analysis to Uncover Socio-Economic Differences Among Spatial-Economics Entities - Ivana Rasic Bakaric (European Regional Science Association (ERSA), 2006)
Main aim of regional policy is to reduce regional disparities. There is now doubt that action to tackle regional disparities is needed in Croatia. Main problem is the definition of region as a subject of regional policy. After discussion about definition of region and main criteria which should be considered during the process of establishment of regions, the paper will present one of the methodologies for spatial-economic entities' classification. The methodology will be used on the working sample of several Croatian counties. The classification will be obtained through use of multivariate statistical methods, and it is based on a wide number of demographic, economic, educations, employment indicators. Results leads to the identification of several axes of socio-economic characterisation, and the division of the observed territory into several homogenous clusters, regions with different degree of development. The main conclusion is that socio-economic reorients uncovered with this methodology provide useful characterisation and division of the territory, for policy making purpose.
Keywords: 330